Determining the number of layers in few‐layer graphene by combining Raman spectroscopy and optical contrast. (16th November 2017) - Bayle, Maxime; Reckinger, Nicolas; Felten, Alexandre; Landois, Périne; Lancry, Ophélie; Dutertre, Bertrand; Colomer, Jean‐François; Zahab, Ahmed‐Azmi; Henrard, Luc; Sauvajol, Jean‐Louis; Paillet, Matthieu
Abstract : Raman spectroscopy is commonly used to determine the number of layers of few‐layer graphene (FLG) samples. In this work, we focus on the criteria based on the G‐band integrated intensity and on the laser optical contrast. Limitations due to stacking order are discussed and lead to the conclusion that it is necessary to combine Raman and optical contrast to avoid misinterpretation. Both methods enable to distinguish unambiguously between single layer graphene and multilayer graphene. However, neither each method separately nor the combination of the two enable a determination of the number of layers for all possible stacking orientations. Importantly, because the two methods always significantly disagree when they fail, the comparison of the values deduced by each method allows to discriminate if the determined number of layers can be specified or not. Other important parameters (substrate, laser wavelength, objective numerical aperture) are discussed to define a reliable method to determine the number of graphene layers in FLG and its domain of validity. The proposed method that combines Raman and optical contrast measurements, carried out with a 532 nm laser and using a 100× objective with a numerical aperture of 0.9, allows the determination of the number of layers for (up to 5) FLG on the following substrates: (1) glass (soda lime glass or similar with refractive index between 1.50 and 1.55) and (2) oxidized silicon (SiO2 on silicon, with a SiO2 thickness of 90 ± 5 nm). The method is however limited to high quality graphene and FLG with small defect density and low residue. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The normalized Raman G‐band integrated intensity combined with the laser optical contrast is investigated as metrics to determine the number of layers of few‐layer graphene. The purpose of this paper is to define the precise experimental conditions (set of parameters) to ensure the reliability and reproducibility of the proposed method and to clearly state its limitations and domain of validity.